IMPLEMENTATION OF MANAGEMENT SYSTEM ON HALAL CERTIFICATION FOR MEDAN CITY MSMES ACTORS: (Case study at the Medan City Cooperative and MSMEs Office) - Divia Zulianti; Nuri Aslami (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
The Medan City Micro, Small and Medium Enterprises (MSME) and Cooperative Service in collaboration with the Halal Product Guarantee Agency (BPJPH) supports the existence of a halal certificate guarantee for MSME actors in the city of Medan. Currently, to implement all of business activity, there is a need for halal certification guarantee management so that MSME business actors can better understand how important a halal certificate is to a business. Indonesia's population is a Muslim-majority country and a potential market for various halal products. The percentage of the number of micro, small and medium enterprises is high. For example, micro businesses can be represented at 98,79%, small businesses 1,11%, while medium businesses 0,09%, and large businesses only 0,01%. This data is based on the 2013 Ministry of Cooperatives and Small and Medium Enterprises and from the total of these business units, micro, small and medium enterprises (MSMEs) act as business drivers in Indonesia. However, the guarantee of a halal certificate issued by the Ministry of Religion is considered to be very difficult for Medan City MSME actors to obtain due too many requirements that must be met by the business actors themselves. The guarantee of a halal certificate is expected to be a spirit to awaken and excite the development of the halal industry in the country, especially North Sumatra. Halal Product Assurance certification and supervision services also consistently apply the principles of integrity, transparency, and avoid all kinds of extortion and gratification.